2017
DOI: 10.1140/epjc/s10052-017-4985-4
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of a crystal collimation test stand at the Large Hadron Collider

Abstract: Future upgrades of the CERN Large Hadron Collider (LHC) demand improved cleaning performance of its collimation system. Very efficient collimation is required during regular operations at high intensities, because even a small amount of energy deposited on superconducting magnets can cause an abrupt loss of superconducting conditions (quench). The possibility to use a crystal-based collimation system represents an option for improving both cleaning performance and impedance compared to the present system. Befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…The crystal length is l Cry 1 = 1.2 cm, which was chosen to have a bending radius R = 80 m, as the present crystals installed in the LHC. This follows the parametric studies reported in [21] and ensures an optimum crystal channeling performance at LHC top energy, while keeping the nuclear interactions rate as low as possible.…”
Section: Ir8 Layout Designsupporting
confidence: 60%
See 2 more Smart Citations
“…The crystal length is l Cry 1 = 1.2 cm, which was chosen to have a bending radius R = 80 m, as the present crystals installed in the LHC. This follows the parametric studies reported in [21] and ensures an optimum crystal channeling performance at LHC top energy, while keeping the nuclear interactions rate as low as possible.…”
Section: Ir8 Layout Designsupporting
confidence: 60%
“…It was therefore decided to design optimised layouts for the existing and already commissioned optics. The same approach was used to design the crystal collimation layout currently installed in the LHC [21], which led to the successful observation of crystal channeling with 6.5 TeV/c protons beams [5].…”
Section: Design Goals Constraints and Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…It contains a high-precision goniometer with sub-µrad accuracy [11] that is mounted on a special tank with an "O" shaped pipe, which can hide the crystal during the standard operational activity of the accelerator. This design was conceived to minimize the impedance of the device for high-intensity The layout of the LHC crystal setup is described in detail in [9]. It was optimized for the operation with proton beams, but it is fully adequate for ion beam tests as well.…”
Section: Layout Of Lhc Crystal Setupmentioning
confidence: 99%
“…In order to study the channeling at the hadron-beam energies relevant for the LHC, and to obtain a direct comparison to the performance of the present LHC collimation system [7], a crystal collimation test stand was installed in 2015 in the betatron collimation insertion [8]. It consists of two crystals, with length of 4 mm along the beam direction and bent to a target design angle of 50 µrad, that enable horizontal and vertical beam collimation tests [9]. 1 Standard LHC collimators, which are part of the LHC betatron cleaning system and are located downstream of the crystals, are used to intercept and probe the channeled halo particles.…”
Section: Introductionmentioning
confidence: 99%